Avaliação morfológica das estruturas anatômicas do canal anal e parede anorretal anterior, utilizando ultrassonografia anorretal tridimensional dinâmica, comparando mulheres com e sem anorretocele - Barreto, Rosilma Gorete Lima (2010)
To evaluate the anatomical constitution of the anal canal and recto-vaginal septum, compared to normal women suffering from rectocele, using dynamic three-dimensional anorectal (Echodefecography). One hundred women with obstructed defecation were prospectively evaluated through Echodefecography, average age 46,64 ± 10,54, with mean validated wexner constipation score 10,87 (range 6,0 - 17,0) within the period from January 2008 to April 2009. All anus rectal disorders were identified and the anatomical structures that make up the anal canal (anterior internal anal sphincter, external anal sphincter, gap, puborectalis - external anal sphincter, posterior internal anal sphincter) were measured and the thickness of the rectal wall and anterior anal canal in the proximal limit of the external anal sphincter, and anorectal junction and at 1,0 cm of the proximal anorectal junction. Then, they were divided into Group I (without rectocele) = 32 patients, Group II (degree I rectocele) = 11 patients, Group III (degree II rectocele) = 27 patients, Group IV (degree III rectocele) = 30 patients, and Group V (degree I + II + III rectocele). All patients formally consented. The length of the gap was significantly lower in group I (21.24 ± 0.97) compared to groups III , IV and V (25,04 ± 0,82 / 23.82 ± 0,80 and 23.92 ± 0.52) respectively (p <0.05). The length of the anterior external anal sphincter was significantly higher in group I (18.91 ± 0.38) compared to group III and V (16,94 ± 0,45 and 17,58 ± 0,29), respectively (p <0.05). The length of the anatomical structures that make up the rectal wall and anterior anal canal showed no statistically significant difference when comparing group I to group II (P> 0.05). There was no significant difference among the five groups regarding to the thickness of the rectal wall and anterior anal canal in limit of external anal sphincter, in the anorectal junction and at 1.0cm proximal to the anorectal junction, as well as the remaining anatomics parameters (p> 0.05). The shorter length of anterior external anal sphincter and consequent increasing in the size of gap are considered the main responsible factors for the formation of rectocele.